International student mobility in crisis? Understanding post-diploma mobility decision-making in an economic crisis context - Cairns, D. (2015)
This article examines student mobility in Portugal, with the aim of understanding what prompts the decision to leave, with particular emphasis upon the weight of factors associated with the on-going economic crisis. Findings from a survey of 400 Lisbon students conducted during 2014 are used to demonstrate the popularity of the idea of moving abroad after the completion of present course of study, with 35% indicating an intention to leave Portugal. Regression analysis confirms that factors associated with the economic crisis have a bearing upon mobility decisions, the most significant predictor being negative impact on personal well-being.